Clicking the Arsenic–Carbon Triple Bond: An Entry into a New Class of Arsenic Heterocycles. Issue 39 (27th July 2016) - Pfeifer, Gregor; Papke, Martin; Frost, Daniel; Sklorz, Julian A. W.; Habicht, Marija; Müller, Christian
Abstract: Arsaalkynes can undergo regioselective and quantitative [3+2] cycloaddition reactions with organic azides to give hitherto unknown 3 H ‐1, 2, 3, 4‐triazaarsole derivatives. The reaction product was obtained as a white, air‐ and moisture‐stable solid, and the presence of a planar, five‐membered arsenic heterocycle was unambiguously verified by means of X‐ray crystallography. DFT calculations gave insight into the electronic structure of these novel compounds compared to tetrazoles and triazaphospholes. The coordination chemistry towards Re I was investigated and compared with the structurally related phosphorus‐containing ligand. These preliminary investigations pave the way for a new class of arsenic heterocycles and fill the gap between the azaarsoles already known. Abstract : A facile route to a new class of arsenic heterocycles has been developed by making use of a [3+2] cycloaddition reaction between an arsaalkyne and an organic azide. The formation of the hitherto unknown air‐ and moisture‐stable triazaarsole was verified by means of single‐crystal X‐ray diffraction (see picture; blue N). A comparison with triazaphospholes gives insight into the structural and electronic properties of this five‐membered ring.